ANALISIS SISTEM PERBANKAN SYARI’AH DI INDONESIA (TELAAH UNDANG-UNDANG NO. 21 TAHUN 2008) - Afriyani Afriyani (Jurnal Bisnis dan Kewirausahaan, 2018)
In examining this title, trying to uncover the one issue, how is the Shariah Banking System in Indonesia as stipulated in Law No.21 of 2008, which is then divided into 3 sub-issues. From the problems mentioned above, then the steps taken to solve the problem is literature research (Liberary research) by using inductive methods coupled with the juridical approach. From the research conducted, it can be seen that the operational system of Syari'ah Banking business activities including Syari'ah Commercial Bank and Syari'ah Sharia Bank (BPRS) in conducting its business activities should not be contradictory to Shari'ah principle, as regulated in UU no. 21 Year 2008 About Syari'ah Banking. Syari'ah Banking fund distribution system to customers, the outline of shari'ah financing products includes 3 principles. And from the operational system of business activities and extension system and Syari'ah Banking, it is emphasized the importance of supervision and supervision on Syari'ah Banking which is formed by special institution as described in Sharia Banking Law. This is based on the fact that customers are very consistent with time and tend to be apathetic with the complicated banking transaction process.